The fictional composition of the conclusion during Bani Al- Ahmar era (a technical analysis study( - / Ali Mtasher Naima/ Kareem Qassim Jaber Al-Rubaie ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Conclusion formed an influential presence in the same Andalusian poet in general, and among the poets of BaniAl- Ahmar (the study sample) in particular, specially figurative formation as an artistic feature because of its importance in the succession of its part and their interrelation. Then, the recipient can easily absorb the text and ease using this formation, and since the conclusion is the solid base on which the poets leans and the abstract which the poet must take care of more than the rest of the poem’s parts, and without it the poem loses its serenitly and its purpose indicative of its content and its being, and its steadfastness to the recipient in terms of ideas and contents and this formation of the conclusion achieved a presentation through its close connection with the other parts of the poem.DOI /10.54633/2333-021-042-011